Wearable cameras can reduce dietary under-reporting: doubly labelled water validation of a camera-assisted 24 h recall. Issue 2 (28th November 2014) - Gemming, Luke; Rush, Elaine; Maddison, Ralph; Doherty, Aiden; Gant, Nicholas; Utter, Jennifer; Ni Mhurchu, Cliona
Abstract : Preliminary research has suggested that wearable cameras may reduce under-reporting of energy intake (EI) in self-reported dietary assessment. The aim of the present study was to test the validity of a wearable camera-assisted 24 h dietary recall against the doubly labelled water (DLW) technique. Total energy expenditure (TEE) was assessed over 15 d using the DLW protocol among forty adults ( n 20 males, age 35 (sd 17) years, BMI 27 (sd 4) kg/m 2 and n 20 females, age 28 (sd 7) years, BMI 22 (sd 2) kg/m 2 ). EI was assessed using three multiple-pass 24 h dietary recalls (MP24) on days 2–4, 8–10 and 13–15. On the days before each nutrition assessment, participants wore an automated wearable camera (SenseCam (SC)) in free-living conditions. The wearable camera images were viewed by the participants following the completion of the dietary recall, and their changes in self-reported intakes were recorded (MP24+SC). TEE and EI assessed by the MP24 and MP24+SC methods were compared. Among men, the MP24 and MP24+SC measures underestimated TEE by 17 and 9 %, respectively ( P < 0·001 and P = 0·02). Among women, these measures underestimated TEE by 13 and 7 %, respectively ( P < 0·001 and P = 0·004). The assistance of the wearable camera (MP24+SC) reduced the magnitude of under-reporting by 8 % for men and 6 % for women compared with the MP24 alone ( P < 0·001 and P < 0·001). The increase in EI was predominantly from the addition of 265 unreported foods (often snacks) as revealed by the participants during the image review. Wearable cameras enhance the accuracy of self-report by providing passive and objective information regarding dietary intake. High-definition image sensors and increased imaging frequency may improve the accuracy further.